Special challenge interprofessional education – how should lecturers be trained? - Schlicker, Andrea; Nitsche, Julia; Ehlers, Jan (Frontiers in Education, 2023)
To enable interprofessional collaboration in practice, it is important to practice interprofessional action during education. Teachers engaged in interprofessional education (IPE) in Germany are insufficiently prepared for joint teaching and often lack pedagogical-didactical training. Teachers, who are used to working uniprofessionally, are expected to teach competently across professions. This overlooks the fact that the admission requirements for teaching at the various institutions such as technical colleges, universities of applied sciences and universities are different. In addition, interprofessional teaching is characterized by a special feature: it should be carried out in team teaching. This poses the challenge for the teachers not only to prepare for the teaching in terms of content, but also to get involved with another teacher. This study asks what interprofessional faculty need to feel well prepared to teach together and focuses on three professions: human medicine, nursing, and physiotherapy. For this purpose, 15 experts were interviewed, five from each of the three professions. The interview material was analyzed according to the structuring qualitative content analysis by Kuckartz (2014), where categories were created to answer the research question. As a result, the analysis showed that three levels are important for the interviewees: the personal prerequisites that contribute to the success of IPE as well as good preparation on a structural and content-related level. Based on this, a concept for further education for interprofessional teachers will be developed.